2005
DOI: 10.1016/j.ejcts.2005.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Extended written pre-operative information about possible complications at cardiac surgery—do the patients want to know?

Abstract: Most, but not all, patients in the present study were positive to the extended written detailed information about risk of complications in connection with cardiac surgery. Detailed information can be a useful base for fruitful conversations between the health care personnel and the patients. The patients and their next of kin are informed, and better prepared if complications occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 23 publications
1
43
2
1
Order By: Relevance
“…In a study by Berger et al, it was found that ICDs that have been prepared in the last 20 years are twice as long as those prepared before. The reason for this is the need to give patients more information and developments of the four subjects mentioned above (18,19).…”
Section: How Should We Increase the Rate Of Reading Icd?mentioning
confidence: 99%
“…In a study by Berger et al, it was found that ICDs that have been prepared in the last 20 years are twice as long as those prepared before. The reason for this is the need to give patients more information and developments of the four subjects mentioned above (18,19).…”
Section: How Should We Increase the Rate Of Reading Icd?mentioning
confidence: 99%
“…As the extended information covers all types of complications, from tiredness to death, it ought to generate thoughts and questions in the patient and their NoK. It has been shown that the extended information serves as a useful basis for fruitful conversations between the health care professionals and the patients and also gives rise to discussions between the patients and their NoK (Ivarsson et al 2005a). …”
Section: Introductionmentioning
confidence: 99%
“…The time from confirmation of the need for cardiac surgery until the operation takes place is a time of worry not only for the patient but also for the next of kin (NoK) (Bengtson et al 1996;Bresser et al 1993;Ivarsson et al 2005a;Ivarsson et al 2005b;Mark et al 1997;Staples and Jeffrey 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta diferencia entre las expectativas de conocimiento y el conocimiento recibido ha sido reportada en varios estudios previos. 92,204 Los pacientes esperan más información en aspectos relacionados con la dimensión biofisiológica y funcional, 92,205,206,207,208 lo que no sorprende debido a la naturaleza de la intervención quirúr-gica. Las cuestiones biofisiológicas generan mayores necesidades de aprendizaje y están relacionadas con los síntomas -como el dolor, las náuseas y los mareos-, y los pacientes deben lidiar con ello después de la cirugía.…”
Section: Expectativas De Conocimiento Y Conocimiento Recibido En El Cunclassified